Skeletal Muscle Index's Impact on Discharge Disposition After Head and Neck Cancer Free Flap Reconstruction - Jones, Alexander Joseph; Campiti, Vincent Joseph; Alwani, Mohamedkazim; Novinger, Leah J; Bonetto, Andrea; Sim, Michael W; Yesensky, Jessica A; Moore, Michael G; Mantravadi, Avinash V (Otolaryngology-head and neck surgery, 2021)
To determine the role of skeletal muscle index (SMI) in the assessment of frailty and determination of discharge to post-acute care facilities (PACF) after head and neck cancer free flap reconstruction (HNCFFR).OBJECTIVETo determine the role of skeletal muscle index (SMI) in the assessment of frailty and determination of discharge to post-acute care facilities (PACF) after head and neck cancer free flap reconstruction (HNCFFR).Retrospective cohort.STUDY DESIGNRetrospective cohort.Single-institution, academic tertiary referral center.SETTINGSingle-institution, academic tertiary referral center.Adult patients undergoing HNCFFR from 2014 to 2019 with preoperative abdominal computed tomography imaging were retrospectively analyzed. Patient demographics, 5-factor modified frailty index (5-mFI), body mass index (BMI), SMI at the third lumbar vertebra, oncologic history, perioperative data, and Clavien-Dindo (CD) complications were collected. Binary logistic regression was used to identify independent predictors of discharge disposition.METHODSAdult patients undergoing HNCFFR from 2014 to 2019 with preoperative abdominal computed tomography imaging were retrospectively analyzed. Patient demographics, 5-factor modified frailty index (5-mFI), body mass index (BMI), SMI at the third lumbar vertebra, oncologic history, perioperative data, and Clavien-Dindo (CD) complications were collected. Binary logistic regression was used to identify independent predictors of discharge disposition.The cohort consisted of 206 patients, 62 (30.1%) of whom were discharged to PACF. Patients discharged to PACF were of older age (65.4 vs 57.1 years, P < .0001) and had a lower SMI (38.8 vs 46.8 cm2/m2, P < .0001), higher 5-mFI (≥3; 25.8% vs 4.2%, P < .0001), and greater incidence of stage IV (80.6% vs 64.1%, P = .0211) aerodigestive cancer (80.6% vs 66.7%, P = .0462). Patients discharged to PACF experienced more blood transfusions (74.2% vs 35.4%, P < .0001), major postoperative complications (CD ≥3, 40.3% vs 12.9%, P < .0001), and delirium (33.9% vs 4.2%, P < .0001). After adjusting for pre- and postoperative factors, multivariate binary logistic regression identified age (P = .0255), 5-mFI (P < .0042), SMI (P = .0199), stage IV cancer (P = .0250), aerodigestive tumor (P = .0366), delirium (P < .0001), and perioperative blood transfusion (P = .0144) as independent predictors of discharge to PACF.RESULTSThe cohort consisted of 206 patients, 62 (30.1%) of whom were discharged to PACF. Patients discharged to PACF were of older age (65.4 vs 57.1 years, P < .0001) and had a lower SMI (38.8 vs 46.8 cm2/m2, P < .0001), higher 5-mFI (≥3; 25.8% vs 4.2%, P < .0001), and greater incidence of stage IV (80.6% vs 64.1%, P = .0211) aerodigestive cancer (80.6% vs 66.7%, P = .0462). Patients discharged to PACF experienced more blood transfusions (74.2% vs 35.4%, P < .0001), major postoperative complications (CD ≥3, 40.3% vs 12.9%, P < .0001), and delirium (33.9% vs 4.2%, P < .0001). After adjusting for pre- and postoperative factors, multivariate binary logistic regression identified age (P = .0255), 5-mFI (P < .0042), SMI (P = .0199), stage IV cancer (P = .0250), aerodigestive tumor (P = .0366), delirium (P < .0001), and perioperative blood transfusion (P = .0144) as independent predictors of discharge to PACF.SMI and 5-mFI are independently associated with discharge to PACF after HNCFFR and should be considered in preoperative planning and assessment of frailty.CONCLUSIONSSMI and 5-mFI are independently associated with discharge to PACF after HNCFFR and should be considered in preoperative planning and assessment of frailty.